Achieving the United Nations Sustainable Development Goals : late or too late? - Ure, John (Emerald Publishing Limited, 2024)
In the decade since the UN SDG agenda was established, how much progress have we really made? What can we be doing to ensure that we're on the right track? Is it too late to meet the 2030 Agenda? Written by John Ure, an economist and academic turned consultant for UN agencies such as the World Bank, the IFC, the ITU, UNDP, UNESCAP, and more, Achieving the United Nations Sustainable Development Goals is an accessible contemporary account of a fast-developing field of literature, evidence, and science around the SDG challenges. Dividing the SDGs into four core themes - poverty, environment, civil society, and global partnerships - Ure delves into the current status of each, identifying the main challenges to be overcome and examining what we can be doing to get there. With policy implications and practical guidelines for building momentum both at an individual and collective level, Ure provides a balanced yet a definitive and compelling assessment of the SDGs. Cutting through the huge volume of literature for each of the SDGs as 2030 closes in, this immensely readable primer makes sense of the state of play for some of the most pressing existential questions of our time. It calls on policymakers, business professionals, educators, NGOs, media professionals, and the public to reevaluate policies and their role in the sustainable development agenda.
Keywords: Sustainable Development Goals (Project); Sustainable development reporting.; Business & Economics -- Development -- Sustainable Development.; Relating to UN Sustainable Development Goals (SDGs); Development economics and emerging economies.; Sustainability.; elektronické knihy; electronic books